Eco-sustainable paper wastewater management by water-resource recovery and concentrate minimization using a membrane oxidation reactor and membrane distillation system - Dogan, Esra Can; Piskin, Elif Durna; Narci, Ali Oguzhan; Kiril Mert, Berna; Yakin, Sevgi Topcu; Demirozlu, Tugba Nur; Atasoy, Mine Selin (Royal Soc Chemistry, 2023)
The aim of this study was to perform the treatment of paper industry raw wastewater by using Fenton or photo-Fenton reaction with a submerged UF process ({Fenton/UF}, {UVA-Fenton/UF}, {UVC-Fenton/UF}) within a MOR to meet current discharge standards and to provide water recovery by producing industrial reuse water with MD. The feasibility of industrial wastewater management was evaluated by feeding the MD concentrates into the MOR inflow at regular intervals. When all three systems are evaluated, the {Fenton/UF} process can be considered to be the most effective MOR operation with a high permeate flux of 875 L m-2 h-1, TOC of 68.0%, COD of 69.2%, and color removal of 32.1%. The TOC, COD, and color average removal efficiencies for the three systems were 87.0 +/- 0.5%, 87.8 +/- 1.2% and 99.6 +/- 0.3% and the MD wastewater could be recovered at a rate of 50-60% for reuse as process water with a permeate flux of approximately 14.6 +/- 0.7 L m-2 h-1. The proposed hybrid physico-chemical treatment technology can be applied as an end-of-pipe approach after making the required pH adjustment to the effluent according to discharge standards after iron recovery. In this study, the hybrid process was proven to be effective in reducing the pollutant levels in paper industry wastewater by entirely meeting discharge standards (central municipal wastewater treatment system or deep-sea remediation). By comprehensively evaluating the experimental studies conducted with MOR-MD and the relevant literature, an eco-sustainable solution proposal that includes comprehensive liquid discharge minimization and resource recovery has been developed. The reclamation of paper wastewater could be accomplished successfully not only to diminish the industrial freshwater demand by process water recovery, but also to efficiently minimize liquid discharge via membrane concentrate treatment and resource (Fe and P) recovery solutions proposed eco-sustainably together in a cleaner and greener wastewater management system. We perform the treatment of paper industry raw wastewater by using Fenton or photo-Fenton reactions with a submerged UF process within a MOR, aiming to meet current discharge standards and to provide water recovery by producing industrial reuse water with MD.
Keywords: Solar Photo-Fenton; Reuse; Pulp; Integration; Separation; Efficiency; Industry; Iron; Removal